Immunocastration in Gilts: A Preliminary Study of the Effect of the Second Dose Administration Time on Growth, Reproductive Tract Development, and Carcass and Meat Quality - Leticia Pérez-Ciria (Animals, 2021)
Increasing fatness and avoiding puberty are desirable in gilts intended for high-quality dry-cured ham production. A total of 48 Duroc x (Landrace x Large White) females of 26.5 ± 3.70 kg body weight (BW) were used to evaluate the impact of immunocastration and to find the optimum application time of the second dose for immunocastration on growth; sex hormones; reproductive tract development; and carcass, meat, and fat quality. Gilts were allocated to four experimental treatments (n = 12): control (entire gilts, EG) and immunocastrated gilts (IG), providing the second dose at 12, 9, or 7 weeks before slaughter (with approximately 60, 75, or 90 kg BW, respectively). Mean slaughter BW was 125 kg. Immunocastrated gilts had lighter reproductive tracts and greater fat thickness than EG. Fat from IG was more saturated and less polyunsaturated than that from EG. Numerically, gilts immunocastrated 9 and 12 weeks before slaughter presented higher fatness than those immunocastrated 7 weeks before slaughter. In conclusion, immunocastration is a good strategy to improve the fatness of gilts destined to dry-cured ham elaboration, with the optimum time for the second dose application seemingly between 9 and 12 weeks before slaughter.